Bibliometric Analysis of Islamic Parenting - Loso Judijanto (Westscience Press, 2026)
Islamic parenting has become an increasingly important research topic due to its role in shaping children's moral development, religious identity, family relationships, and educational practices. However, the intellectual structure, development trends, and emerging themes within Islamic parenting research remain fragmented across various academic disciplines. This study aims to provide a comprehensive mapping of Islamic parenting research through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to Islamic parenting, Muslim parenting, Islamic education, and family studies. The collected publications were analyzed using VOSviewer to examine publication trends, influential literature, author collaboration networks, country collaborations, citation patterns, and keyword co-occurrence structures. The findings reveal that Islamic parenting research has developed from early discussions focusing on cultural perspectives, religious values, and parent-child relationships toward broader contemporary issues involving Islamic education, digital parenting, family resilience, and child development challenges. Citation analysis identifies several influential studies that provide theoretical foundations for understanding the relationship between cultural context, Islamic values, and parenting practices. The collaboration analysis highlights Indonesia as the most prominent contributor, with growing international connections involving Malaysia, the United Kingdom, China, Austria, and Sudan. Keyword analysis demonstrates that the field is primarily centered around parenting, Islam, parents, child-parent relationships, and Islamic education, while emerging themes indicate increasing scholarly attention toward technology, family adaptation, and children's social well-being. This study contributes to a deeper understanding of the evolution and future directions of Islamic parenting research by identifying knowledge patterns, research gaps, and potential opportunities for interdisciplinary development.